Judicial Red Tapism Towards the Appeals of Death Cell’s Prisoners: A Case Study of Central Adiala Jail Rawalpindi - Amjid, Ihtisham; Mashud, Nasim Khan (Social Science Review Archives, 2025)
Pakistan's criminal justice system has traditionally been slow and inefficient, notably for death penalty cases. This study explores how court red tape bureaucratic inaction, procedural delays, and administrative bottlenecks affects death row prisoner appeals. The study examined how procedural delays in the appeal system effect death row prisoners' mental health, how judicial and administrative inefficiencies play a role, and how to speed up and make legal proceedings fair based on evidence. A structured interview schedule was used to acquire quantitative data from 35 death row prisoners at Central Adiala Jail. Determine variable relationships using descriptive statistics (mean and standard deviation), inferential statistics (correlation and regression), and chi-square tests. Delayed appeal outcomes were strongly linked to severe mental distress like worry, depression, and hopelessness. Legal help was usually poor, and administrative issues including not getting case updates and bureaucratic red tape caused prolonged detention. Regression analysis showed that administrative issues were the strongest predictor of prisoner psychological distress. The findings demonstrate the necessity to reform the courts. We need to fast-track death penalty appeals, ensure everyone gets the same legal help, improve prisoner communication, and provide psychological support. Without systemic improvements, judicial red tape will prevent justice, violate human rights, and trap the most vulnerable in prison.